USE OF NON-INSTRUMENTAL LIE DETECTION METHODS BY OPERATIVE EMPLOYEES OF OPERATIVE AND INVESTIGATIVE BODIES - Dyakova, Julia; Litvinova, Iryna (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: the article is aimed at the study and analysis of the practices of using non-instrumental methods of detecting lies, which are used by operatives of investigative agencies. The article will consider the main types of non-instrumental methods, such as facial expressions, gestures, non-verbal signs of stress, etc., as well as their features and advantages. Results: the importance and high potential of using non-instrumental methods of lie detection by operatives was established. The study shows the effectiveness of these methods for detecting false information and suspicious behavior of persons associated with criminal activities. However, the study emphasizes the need for a careful approach to the use of non-instrumental lie detection and combining it with other methods. Discussion: non-instrumental lie detection in the work of operatives, which consists in the analysis of non-verbal cues such as facial expressions, gestures, tone of voice and body language. Today, there are many methods of detecting false information based on human behavior, so having this knowledge is a valuable resource for operatives. It is important to understand that non-instrumental lie detection should be complemented by other methods of work in operational and investigative activities, such as information analysis, interrogation, evidence analysis, etc. Combining different methods will help provide a more complete and accurate understanding of the situation. When using non-instrumental lie detection, operatives must have appropriate training and practical experience to use the tool effectively. Controlling emotions and interacting with the person at a level that will create a favorable basis for communication are also important in this process. Non-instrumental lie detection is an important element in the set of tools that operatives can use to effectively perform investigative actions and obtain reliable information.